Microcontroller Based Anti Sleep Alarm System - Ahmad, Adnan; Sharma, Anjali; Singh, Astha; Chatterjee, Sumanta; Paul, Apurba (International Journal of Computer Sciences and Engineering, 2020)
With the predictions of the world Health Organization (WHO) that number of deaths due to traffic accidents will be around 2 million in next 15 years. Researchers nowadays are paying more attention in preventing traffic accidents and lower the number of occurred fatalities. The purpose of this work is an attempt to prevent traffic accidents due to fatigue or sleepiness of the driver. In this work we developed a customized goggles, which is microcontroller based anti sleep alert system for the drivers. In this device the inbuilt infrared sensor detect the obstacle and transfer signal to Arduino then Arduino supply signal to buzzer. This device can be used by the physical paralysed person to communicate with others, can be used by the security personnel at night and can also be used by the patient in comma